Aplikasi Pendataan Prohibited Item Divisi Keamanan Penerbangan Bandara Kualanamu - Wibowo, Dimas Achmad; Fajrul Hukmi Poetra (Yayasan Literasi Sains Indonesia, 2023)
Current technological developments can be said to be growing very rapidly, starting from small devices such as mobile phones, to computer devices which are increasingly developing over time and are increasingly able to meet human needs with access that is very easy for users to understand. As technological progress continues to accelerate in this day and age, Almost all data collection, whether inventory or anything else, already uses a computerized system. There are many benefits to be gained from the computerization of a system, including the resulting data being more accurate, reducing errors when entering data, and more time efficiency, faster and more practical. This is the author's reference for building an application that can record all items that are detained or scattered in the Kualanamu airport security inspection area. All items that will be data that were previously entered manually are computerized. It is hoped that this application will be able to help and reduce data entry errors that have occurred so far. The author created a Prohibited Item data collection system and monthly reports that make it easier for passengers if they later want to take back items that have been detained